2020
DOI: 10.1080/15502724.2020.1803752
|View full text |Cite
|
Sign up to set email alerts
|

Procedure for Measuring the Luminance of Roadway Billboards and Preliminary Results

Abstract: Advertising media installed in the vicinity of the road may pose a potential threat to road safety. The driver's perception of advertising depends on a number of factors, including the time of day, the location and dimensions of the medium, the luminance value, and the way the light is emitted. However, the excessive or incorrect distribution of media luminance in the driver's field of vision, especially at night, may have a significant effect on the disturbance of the visual process. The driver's night vision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Luminance Ratio [10,21] Luminance Contrast is the comparison between the luminance in target and luminance background. 6…”
Section: Parametersmentioning
confidence: 99%
“…Luminance Ratio [10,21] Luminance Contrast is the comparison between the luminance in target and luminance background. 6…”
Section: Parametersmentioning
confidence: 99%
“…The previous studies found that the impact of billboards on driving performance varies depending on the billboards' and drivers' characteristics [6,21,22]. Characteristics of the billboard include the type of display [11,23,24], the content of the display [25][26][27][28], and the level of illumination [29,30]. Driver characteristics includes age [31][32][33], and gender [31,32,34].…”
Section: Roadside Advertisement/billboardmentioning
confidence: 99%
“…Recently, Tomczuk et al (2020) [29] conducted pilot field studies to determine whether excessive brightness of media is a problem in Poland country and what percentage of media is affected. The light parameters (carrier luminance, background luminance, and contrast) and geometric dimensions of 227 billboards' surfaces were measured.…”
Section: Level Of Illuminationmentioning
confidence: 99%
“…The impact of use [29], operation and power supply [30,31] conditions, including the impact of unfavorable external [32][33][34][35], and internal [36] environmental factors (e.g., low-frequency electromagnetic field) on electronic telematics [37][38][39][40] and security systems can be described through, e.g., a change in the intensity of damage to λ components making up a specific system [41,42]. Telematics and security systems and equipment operated in the container contain a large number of active and passive elements.…”
Section: Analysis Of the Security System Operating Process In Terms O...mentioning
confidence: 99%